(untitled) (Singaporean Journal of Business Economics and Management, 2020)
Adoptions of improved crop varieties like improved Teff varieties (Quncho) have an impact for increasing agricultural productivity and improving the food security status of smallholder farmers in Ethiopia. To get the expected benefit, the technology should be adopted well by smallholder farmers. However, the rate of adoption of improved varieties in the country has remained low. The main objective of the current study was to examine factors affecting adoption of improved Teff varieties (Quncho) at farm level in non-traditional Teff growing areas of Benishangul-Gumuz Region of Western Ethiopia. In addition, the study looks in to preferences of small-holder farmers to varietal attributes that determine the adoption of Teff varieties in the study area. In this study, multistage sampling techniques were employed to select sampled households from two districts. About 249 smallholder farmers were selected randomly from nine kebele administrations proportionally. Both qualitative and quantitative types of data were used. Primary data was collected by using semi-structured questionnaire and personal interview, focus group discussion and key informant interview was used to collect the data. Both descriptive and inferential statistics (Tobit estimation model and propensity score matching (PSM)) were used to analyze the data. In 2015/16 production season, about 58.23% of the sampled household were adopters 41.77% of them didn’t adopt improved Teff varieties in the study area. The empirical evidence showed that dependent members of the households, land allocated to cereal and horticultural crops had negative and significance effect on area under improved Teff varieties, while livestock ownership (heifer and poultry), access to training and information on Teff, being progressive farmer and social networks have contributed positively and significantly to Teff adoption. The PSM results indicated that adoption of improved Teff varieties had significant impact on Teff productivity of adopters as compared to the non-adopters with increased Teff productivity over 276.6 kg/ha. Moreover, the average treatment effect on the treated (ATT) on productivity of Teff is 656.43 kg while the controls groups harvested around 379.82 kg. The average treatment effect on the treated (ATT) of Teff productivity is greater compared to the non-adopters that has brought about 42.14%, indicating change for being participated on improved Teff production compared to non-users. The Tobit model estimation results showed that improved teff varieties adoption decision of farm households has been determined by access to training and information on new improved teff varieties, social networks with friends, neighbors and relatives, capacity building of farmers being a model in the village, ownership of tropical livestock (poultry and heifers) unit, income gained from teff sale and other institutional and socio-economic factors in the study area. The finding of this study suggest that farmers in the area seek awareness and training on new improved teff varieties, need improving livestock ownership and social networks and access to information and enterprise choices.